Rotational effects on the dissociation dynamics of CHD3 on Pt(111) - Füchsel, Gernot; Thomas, Phillip S.; Uyl, Jurriaan den; Öztürk, Yesim; Nattino, Francesco; Meyer, Hans-Dieter; Kroes, Geert-Jan (Physical chemistry, chemical physics, 2016)
Dissociation of methane on metal surfaces is of high practical and fundamental interest. Therefore there is currently a big push aimed at determining the simplest dynamical model that allows the reaction dynamics to be described with quantitative accuracy using quantum dynamics. Using five-dimensional quantum dynamical and full-dimensional ab initio molecular dynamics calculations, we show that the CD3 umbrella axis of CHD3 must reorient before the molecule reaches the barrier for C-H cleavage to occur in reaction on Pt(111). This rules out the application of the rotationally sudden approximation, as explicitly shown through a comparison with calculations using this approximation. Further, we suggest that the observed umbrella swing should strongly affect the sensitivity of C-H cleavage to the initial alignment of the molecule relative to the surface as found experimentally for closely related systems. We find very large differences in reactivity for molecules pre-excited to different rotational states, particularly if these states are associated with different orientations of the C-H bond.